Palmitoylethanolamide Ameliorates Carbon Tetrachloride-Induced Liver Fibrosis in Rats - Ohara, Masatsugu; Ohnishi, Shunsuke; Hosono, Hidetaka; Yamamoto, Koji; Fu, Qingjie; Maehara, Osamu; Suda, Goki; Sakamoto, Naoya (Frontiers in Pharmacology, 2018)
Background. Liver fibrosis is a complex inflammatory and fibrogenic process, and the progression of fibrosis leads to cirrhosis. The only therapeutic approaches are the removal of injurious stimuli and liver transplantation. Therefore, the development of anti-fibrotic therapies is desired. Palmitoylethanolamide (PEA) is an endogenous fatty acid amide belonging to the N-acylethanolamines family and contained in foods such as egg yolks and peanuts. PEA has therapeutic anti-inflammatory, analgesic, and neuroprotective effects. However, the effects and roles of PEA in liver fibrosis remain unknown. Here we investigated the therapeutic effects of PEA in rats with liver fibrosis. Methods. We conducted in vitro experiments to investigate the effects of PEA on the activation of hepatic stellate cells (HSCs, LX-2). Liver fibrosis was induced by an intraperitoneal injection of 1.5 mL/kg of 50% carbon tetrachloride twice a week for 4 weeks. Beginning at 3 weeks, PEA (20 mg/kg) was intraperitoneally injected thrice a week for 2 weeks. Then rats were sacrificed and we performed histological and quantitative reverse-transcription polymerase chain reaction analyses. Results. The expression of α-smooth muscle actin (SMA) induced by transforming growth factor (TGF)-β1 in HSCs was significantly downregulated by PEA. PEA treatment inhibited the TGF-β1-induced phosphorylation of SMAD2 in a dose-dependent manner, and upregulated the expression of SMAD7. The reporter gene assay demonstrated that PEA downregulated the transcriptional activity of the SMAD complex upregulated by TGF-β1. Administration of PEA significantly reduced the fibrotic area, deposition of type I collagen, and activation of HSCs and Kupffer cells in rats with liver fibrosis. Conclusions. Activation of HSCs was significantly decreased by PEA through suppression of the TGF-β1/SMAD signaling pathway. Administration of PEA produced significant improvement in a rat model of liver fibrosis, possibly by inhibiting the activation of HSCs and Kupffer cells. PEA may be a potential new treatment for liver fibrosis.